2016
DOI: 10.1007/s11999-015-4388-5
|View full text |Cite
|
Sign up to set email alerts
|

Success of Pavlik Harness Treatment Decreases in Patients ≥ 4 Months and in Ultrasonographically Dislocated Hips in Developmental Dysplasia of the Hip

Abstract: Background Treatment of developmental dysplasia of the hip (DDH) using the Pavlik harness has been a widely used method in patients between 0 and 6 months of age for many years. However, the factors influencing the success rate of this treatment modality have still not exactly been determined as a result of the limited number of clinical studies with higher level of evidence. Questions/purposes We, therefore, asked whether (1) patient-related variables such as age, gender, and laterality; coexisting risk facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
90
3
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(107 citation statements)
references
References 32 publications
6
90
3
5
Order By: Relevance
“…In our study, the overall proportion of patients experiencing Pavlik harness failure was 14% (30 of 215 hips), 27% (21 of 78 hips) for patients with Ortolani-positive hips, 5% (three of 60 hips) for patients with Barlow-positive hips, and 5% (four of 77 hips) for patients with stable ultrasound-dysplastic hips. Our findings were similar to those of previous studies indicating that a high proportion of Barlow-positive hips and stable ultrasounddysplastic hips can be treated successfully with the Pavlik harness [6,8,12,14,19,25,31]. Despite our strict protocol, the rate of failure in Ortolani-positive hips was similar to those of previous studies reporting a 30% to 60% incidence of treatment failure in dislocated hips [2,16,19,20,24,31,32].…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…In our study, the overall proportion of patients experiencing Pavlik harness failure was 14% (30 of 215 hips), 27% (21 of 78 hips) for patients with Ortolani-positive hips, 5% (three of 60 hips) for patients with Barlow-positive hips, and 5% (four of 77 hips) for patients with stable ultrasound-dysplastic hips. Our findings were similar to those of previous studies indicating that a high proportion of Barlow-positive hips and stable ultrasounddysplastic hips can be treated successfully with the Pavlik harness [6,8,12,14,19,25,31]. Despite our strict protocol, the rate of failure in Ortolani-positive hips was similar to those of previous studies reporting a 30% to 60% incidence of treatment failure in dislocated hips [2,16,19,20,24,31,32].…”
Section: Discussionsupporting
confidence: 90%
“…Although the incidence and risk factors associated with Pavlik harness failure have been reported, previous studies may have been limited by lack of complete assessment of patient factors such as clinical examination [14,19,20,24,31,32] and failure to review ultrasound findings at the time of diagnosis [13,31,32]. We found that failure of Pavlik harness treatment was greatest among patients with Ortolani-positive hips and that male sex and Graf classification were associated with failure of treatment.…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations